2022
DOI: 10.30541/v51i4iipp.161-183
|View full text |Cite
|
Sign up to set email alerts
|

Firm Performance and the Nature of Agency Problems in Insiders-controlled Firms: Evidence from Pakistan

Abstract: More than two centuries ago, Adam Smith (1776) showed skepticism about the efficiency of joint stock companies because of the separation of management from ownership. He observed that managers of joint stock companies cannot be expected to watch over the business with the same anxious vigilance as owners in a partnership would. Adam Smith’s worry remained buried for a century and a half until Berle and Means (1932) rekindled interest in this area when they hypothesised in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 61 publications
2
27
0
Order By: Relevance
“…5 The sample comprehensively covers almost all the non-financial sectors. In order to make our results comparable with earlier studies, the study excludes financial service firms like mutual funds, commercial and investment banks, insurance companies, etc., as well as government and foreign subsidiaries (Shah, 2009;Abdullah, Shah, Iqbal, & Gohar, 2011a;Abdullah, Shah & Khan, 2012;Arshad & Javid, 2014;Yousaf & Hasan, 2016). Group firms are defined on the basis of certain criteria including cross-ownerships and pyramids, cross-directorate-ships and social ties 6 .…”
Section: Methodsmentioning
confidence: 99%
“…5 The sample comprehensively covers almost all the non-financial sectors. In order to make our results comparable with earlier studies, the study excludes financial service firms like mutual funds, commercial and investment banks, insurance companies, etc., as well as government and foreign subsidiaries (Shah, 2009;Abdullah, Shah, Iqbal, & Gohar, 2011a;Abdullah, Shah & Khan, 2012;Arshad & Javid, 2014;Yousaf & Hasan, 2016). Group firms are defined on the basis of certain criteria including cross-ownerships and pyramids, cross-directorate-ships and social ties 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Larger size of the board through resource enrichment theory enhance corporate value by instituting managerial effectively in corporate management [29]. The large size of the board has capacity to pragmatically supervise the activities of the management capable of improving corporate valuation [30]. The complexities in corporate management requires mixtures of expertise in the composition of the board for smooth operations and managerial control needed for value creation.…”
Section: Board Sizementioning
confidence: 99%
“…Van den Berghe and Levrau (2004) argued that resource enrichment theory favors the large board size that increases the value of firm because members have managerial talent and they perform their duties effectively. There is also a view point that large board size has more control on top management and directors can prudently monitor the management performance and duties, which will eventually increase the value of the firm (Abdullah et al, 2012). The advocates of large board size suggested that firms that are large in size and complex require more expertise of their directors.…”
Section: Board Sizementioning
confidence: 99%